The Palaeo-Eskimo Prehistory of the North Devon Lowlands - Helmer, James W. (ARCTIC, 1991)
In this paper the distinguishing characteristics of six chronologically discrete Palaeo-Eskimo occupations discovered in the North Devon Lowlands region of Devon Island, Northwest Territories, are summarized and their cultural/chronological positions briefly assessed. Observed variations in the intensity of occupation in the study area and major shifts in the extra-regional cultural affiliations of these six occupational episodes are discussed in reference to a high-mobility subsistence/settlement strategy model of High Arctic Palaeo-Eskimo socioecological adaptations.Key words: Arctic, Devon Island, prehistory, Palaeo-Eskimo, Pre-Dorset, Dorset Mots clés: Arctique, île Devon, préhistoire, paléo-esquimau, pré-Dorset, Dorset